Spatiotemporal distributions of pair production and cascade in solid targets irradiated by ultra-relativistic lasers with different polarizations. (10th April 2018) - Yuan, T; Yu, J Y; Liu, W Y; Weng, S M; Yuan, X H; Luo, W; Chen, M; Sheng, Z M; Zhang, J
Abstract: Two-dimensional particle-in-cell simulations have been performed to study electron-positron pair production and cascade development in single ultra-relativistic laser interaction with solid targets. The spatiotemporal distributions of particles produced via QED processes are illustrated and their dependence on laser polarizations is investigated. The evolution of particle generation displays clear QED cascade characters. Studies show that although a circularly polarized laser delays the QED process due to the effective ion acceleration, it can reduce the target heating and confine high-energy charged particles, which leads to deeper QED cascade order and denser pair plasma production than linearly polarized lasers. These findings may benefit the understanding of the coming experimental studies of ultra-relativistic laser target interaction in the QED dominated regime.